Correlation analysis of indicators of physical and technical preparedness karate school age - Sklyar, M. S. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: identification of basic indicators of physical qualities at karate school age. Material : in the experiment involved 30 students, ages 16-18 years, with experience training Shotokan Karate 10 years. Results : the density of the relationship of indicators of physical and technical preparedness of the students of the senior classes of secondary school, with long experience of employment Shotokan Karate. Results identified training standards regulated program of physical culture for secondary schools (grades 10-11) and technical characteristics often performed percussion techniques in competitive fights in Shotokan Karate using techniques and specialized shock chronodynamometry ergometer. Correlation analysis revealed that the greatest influence on the formation of shock art of karate techniques at this age is the level of development of high-speed capacity, endurance, strength, complex muscle groups and mobility in the hip joint. Conclusions : the landmark data indicators positively affects the formation of karate techniques.